2003
DOI: 10.1046/j.1365-8711.2003.06538.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden starbursts in Seyfert 1 galaxies

Abstract: We report the detection of the 3.3‐μm polycyclic aromatic hydrocarbon (PAH) feature in two Seyfert 1 galaxies (NGC 3227 and Mrk 766) and one QSO (Mrk 478), observed with SpeX at the Infrared Telescope Facility at a spectral resolution not previously attained for these types of objects. Except for NGC 3227, this is the first time that the 3.3‐μm PAH emission has been detected in Mrk 766 and 478. The widths of the emission, reported also for the first time, are rather similar, ranging from 450 to 550  Å. The lum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…Infrared slit spectroscopy at >3 µm using ground-based telescopes is one of the most powerful tools for selecting such almost pure AGNs, because the presence of nuclear starburst activity can be investigated by polycyclic aromatic hydrocarbon (PAH) emission features, which are not emitted from AGNs but can be produced from nuclear starbursts occurring at a location sufficiently shielded from the AGN's X-ray radiation (Voit 1992;Moorwood 1986;Genzel et al 1998;Roche et al 1991;Imanishi & Dudley 2000;Esquej et al 2014). We have performed extensive ground-based infrared 3-4 µm (L-band) spectroscopy of optical Seyfert nuclei using narrow (<1.6 ′′ ) slits (Imanishi 2002(Imanishi , 2003Rodriguez-Ardila & Viegas 2003;Imanishi & Wada 2004;Imanishi 2006;Imanishi et al 2011a), and identified a large number of AGNs with undetectable nuclear starburst signatures. Our next step is to further select nuclear-starburstfree AGNs which, with ALMA, are expected to emit a detectable amount of molecular emission lines.…”
Section: Targetsmentioning
confidence: 99%
“…Infrared slit spectroscopy at >3 µm using ground-based telescopes is one of the most powerful tools for selecting such almost pure AGNs, because the presence of nuclear starburst activity can be investigated by polycyclic aromatic hydrocarbon (PAH) emission features, which are not emitted from AGNs but can be produced from nuclear starbursts occurring at a location sufficiently shielded from the AGN's X-ray radiation (Voit 1992;Moorwood 1986;Genzel et al 1998;Roche et al 1991;Imanishi & Dudley 2000;Esquej et al 2014). We have performed extensive ground-based infrared 3-4 µm (L-band) spectroscopy of optical Seyfert nuclei using narrow (<1.6 ′′ ) slits (Imanishi 2002(Imanishi , 2003Rodriguez-Ardila & Viegas 2003;Imanishi & Wada 2004;Imanishi 2006;Imanishi et al 2011a), and identified a large number of AGNs with undetectable nuclear starburst signatures. Our next step is to further select nuclear-starburstfree AGNs which, with ALMA, are expected to emit a detectable amount of molecular emission lines.…”
Section: Targetsmentioning
confidence: 99%
“…2), which also includes emission from much larger dust grains. Although the Infrared Astronomical Satellite (IRAS ) aperture is larger than those on IRS, it has been widely demonstrated that the 12-100 m fluxes in star-forming galaxies are dominated by emission from the nuclear regions of the galaxy that also give rise to the PAH emission (Imanishi 2003;Rodriguez-Ardila & Viegas 2003). A preliminary analysis of the 70 m MIPS images of our sample of galaxies shows that for six of the seven high-metallicity starbursts included in Figure 2 ( M82, NGC 7714, NGC 3049, NGC 1482, NGC 253, andNGC 2903), the FIR emission is more extended than the IRS aperture through which the PAH emission is measured.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…To summarize, the 3.3 m band has been a useful tracer of star formation on fairly small scales ($60 to a few hundred parsecs) in AGNs (Imanishi 2002(Imanishi , 2003Rodríguez-Ardila & Viegas 2003;Imanishi & Wada 2004). However, if NGC 1097 turns out to be typical, the combined effects of AGN continuum and the radiation field of stellar clusters themselves probably mean that it is unlikely that the 3.3 m feature will be as useful a diagnostic of vigorous star formation occurring on the smallest (few parsec) scales.…”
Section: The Lack Of Strong Pah Emission At the Nucleusmentioning
confidence: 99%
“…Indeed, some or all of the nuclear obscuration has been proposed to arise in dusty clouds ejected from such starbursts (Cid Fernandes & Terlevich 1995;Fabian et al 1998;Watabe & Umemura 2005) or in optically thick stellar winds (Zier & Biermann 2002). Observationally, young stars are found quite commonly in the inner few hundred parsecs of AGNs (e.g., González Delgado et al 1998;Storchi-Bergmann et al 2000;Imanishi 2002;Imanishi 2003;Rodríguez-Ardila & Viegas 2003).…”
Section: Introductionmentioning
confidence: 99%